荧光差异双向凝胶电泳筛选肾透明细胞癌及癌旁组织中的差异表达蛋白 (Nan Fang Yi Ke Da Xue Xue Bao, 2017)
OBJECTIVE: To identify specific protein markers for renal cell carcinoma detection and diagnosis, as well as develop new potential therapeutic targets of the disease. METHODS: We used two-dimensional difference in-gel electrophoresis (2-D DIGE) technique conjunction with mass spectrometry (MS) for the identification of significant differentially expressed proteins between 15cases of paired clear cell renal cell carcinoma (ccRCC) and adjacent normal renal tissues. The protein spots were considered as differentially expressed if a 1.5-fold altered expression level was observed (Student's t test, P value < 0.05). RESULTS: Of the 27 differentially expressed protein spots, 26 proteins were successfully identified. 11 proteins up-regulated in renal cell carcinoma, 15 proteins down-regulated. Among them Short/branched chain specific acyl-CoA dehydrogenase, mitochondrial (ACDSB), Aldose 1-epimerase (GALM), Peroxiredoxin-4 (PRDX4), Macrophage-capping protein (CAPG), Beta-defensin 107 (D107A), Microfibril-associated glycoprotein 4 (MFAP4) were first time screening as new differential expressed proteins by protomic study in renal cell carcinoma. Conclusions 2-D DIGE is a useful technique for screening and analysis differential expressed proteins in renal cell carcinoma. These new differently expressed proteins may be useful for development new molecular markers for the tumor.